Liposomal and Ethosomal Gels for the Topical Delivery of Anthralin: Preparation, Comparative Evaluation and Clinical Assessment in Psoriatic Patients - Dina Fathalla; Eman M. K. Youssef; Ghareb M. Soliman (MDPI AG, 2020)
To enhance anthralin efficacy against psoriasis and reduce its notorious side effects, it was loaded into various liposomal and ethosomal preparations. The nanocarriers were characterized for drug encapsulation efficiency, size, morphology and compatibility between various components. Optimum formulations were dispersed in various gel bases and drug release kinetics were studied. Clinical efficacy and safety of liposomal and ethosomal Pluronic®F-127 gels were evaluated in patients having psoriasis (clinicaltrials.gov identifier is NCT03348462). Safety was assessed by recording various adverse events. Drug encapsulation efficiency ≥97.2% and ≥77% were obtained for liposomes and ethosomes, respectively. Particle sizes of 116 to 199 nm and 146 to 381 nm were observed for liposomes and ethosomes, respectively. Fourier-Transform infrared (FT-IR) spectroscopy and differential scanning calorimetry (DSC) studies confirmed the absence of interaction between anthralin and various nanocarrier components. Tested gel bases showed excellent ability to sustain drug release. At baseline, the patients had a median Psoriasis Area and Severity Index (PASI) of 3.4 for liposomes and 3.6 for ethosomes without significant difference. After treatment, mean PASI change was −68.66% and −81.84% for liposomes and ethosomes, respectively with a significant difference in favor of ethosomes. No adverse effects were detected in both groups. Anthralin ethosomes could be considered as a potential treatment of psoriasis.